Kształtowanie obciążeń podatkowych na etapie planowania inwestycji - Krzeszowski, Wojciech Dawid (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
There are various views on corporate objectives in business theory and practice. Maximising profit or cash-flow, increase in the goodwill value, maintaining financial liquidity, etc. are listed as some objectives. Tax payments are inextricably linked to the aforementioned issues. The following paper is focused on tax charges planning at a point of deciding about the profitability of an investment project. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1080, s. 173-180